On a two (nonlocal) point boundary value problem of arbitrary (fractional) orders integro-differential equation - Hamad, Wisam; El-sayed, A.M.A; Tantawy, O.E (JOURNAL OF ADVANCES IN MATHEMATICS, 2015)
Here we study the existence of solutions of the functional integral equation: As an application we study the existence of solution of a two (nonlocal) point boundary value problem of arbitrary (fractional) orders integrao-dierential equation.